2006
DOI: 10.2298/tsci0601099n
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of air refrigerator on exergy graph

Abstract: Improving mechanical system efficiency is the goal of many engineers and scientists. Commonly, the solutions to these types of problems are uncovered using thermodynamic analysis and optimization. An innovative method for the thermodynamic analysis of a complex energy-intensive system with an arbitrary structure is described in this paper. The method is based on a novel general equation to calculate the total system exergy efficiency using an exergy flow graph proposed by the authors. Discuss in this paper exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The exergy topological method developed by Nikulshin et al [43][44][45] was used to present a quantitative estimation of the exergy destroyed in an organic Rankine cycle (ORC) operating on R113. A detailed roadmap of exergy flow is presented using an exergy wheel diagram [1] and parameters such as degree of thermodynamic perfection, exergy efficiency, and influence coefficient were evaluated and compared for both ORC configurations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exergy topological method developed by Nikulshin et al [43][44][45] was used to present a quantitative estimation of the exergy destroyed in an organic Rankine cycle (ORC) operating on R113. A detailed roadmap of exergy flow is presented using an exergy wheel diagram [1] and parameters such as degree of thermodynamic perfection, exergy efficiency, and influence coefficient were evaluated and compared for both ORC configurations.…”
Section: Discussionmentioning
confidence: 99%
“…7. Finally, it can be concluded that the methodology proposed by Nikulshin et al [43][44][45] was successfully adapted to analyze the performance of ORC and it could be adapted to evaluate even more complex, energyintensive system configurations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The components are considered as nodes or elements of a network where they are linked by pipes and valves. More details on this approach can be found in [48][49][50][51]. For components and systems performance evaluation, energy efficiency model and other models developed by Nikulshin et al [51]: exergy loss model (EXL) and exergy efficiency model (EEF) will be used.…”
Section: Modelingmentioning
confidence: 99%
“…Var i ous meth od ol o gies have been sug gested in the lit er a ture as ways to pur sue this ob jec tive, based on dif fer ent ap proaches [6]. In the last de cades, the de vel op ment of exergoeconomics has been impres sive in more than one di rec tion and the use ful ness of this con cept was ac knowl edged by a large num ber of schol ars and the de vel op ment is still con tin u ing to day [19,20]. Exergoeconomic can play a vi tal role in the anal y sis, de sign, and op ti mi za tion of ther mal systems.…”
Section: Introductionsmentioning
confidence: 99%